Simplified footprint-free Cas9/CRISPR editing of cardiac-associated genes in human pluripotent stem cells - Kondrashov, Alexander; Hoang, Minh Duc; Smith, James G.W.; Bhagwan, Jamie R.; Duncan, Gary; Mosqueira, Diogo; Barbadillo Munoz, Maria; Vo, Nguyen T.N.; Denning, Chris (Mary Ann Liebert, 2018)
Modelling disease with hPSCs is hindered because the impact on cell phenotype from genetic variability between individuals can be greater than from the pathogenic mutation. While ‘footprint-free’ Cas9/CRISPR editing solves this issue, existing approaches are inefficient or lengthy. Here, a simplified PiggyBac strategy shortened hPSC editing by 2 weeks and required one round of clonal expansion and genotyping rather than two, with similar efficiencies to the longer conventional process. Success was shown across 4 cardiac-associated loci (ADRB2, GRK5, RYR2, ACTC1) by genomic cleavage and editing efficiencies of 8-93% and 8-67%, respectively, including mono- and/or bi-allelic events. Pluripotency was retained, as was differentiation into high purity cardiomyocytes (CMs; 88-99%). Using the GRK5 isogenic lines as an exemplar, chronic stimulation with the beta-adrenoceptor agonist, isoprenaline, reduced beat rate in hPSC-CMs expressing GRK5-Q41 but not GRK5-L41; this was reversed by the beta-blocker, propranolol. This shortened, footprint-free approach will be useful for mechanistic studies.